Glucocorticoid‐Induced Proliferation in Untreated Pediatric Acute Myeloid Leukemic Blasts. Issue 8 (19th April 2016) - Klein, Kim; Haarman, Eric G.; de Haas, Valerie; Zwaan, Ch. Michel; Creutzig, Ursula; Kaspers, Gertjan L.
Abstract : We evaluated the in vitro glucocorticoid (GC) responsiveness of 117 pediatric acute myeloid leukemia cells by considering GC resistance, GC‐induced proliferation, and GC‐induced differentiation. None of the samples was highly GC sensitive, and only 15% were intermediately sensitive. GC‐induced differentiation was not observed, while GC‐induced proliferation was observed in 27% of the samples. Samples with French‐American‐British classification (FAB) type M5 or activating Fms‐like tyrosine kinase 3 (FLT3) mutations were significantly more prone to this phenomenon. Although we could not confirm this in our study, if induced proliferation in vitro is paralleled in vivo, GCs during consolidation may have adverse effects on minimal residual leukemic cells, which might increase relapse risk.